Solvent abuse, toluene acidosis and diabetic ketoacidosis. Issue 1 (March 1991) - Brown, J H; Hadden, D R; Hadden, D S
Abstract : Solvent abuse in adolescents and young adults has been reported to cause a metabolic acidosis with a normal or increased anion gap (Streicher et al., 1981; Voights & Kaufman, 1983, Anonymous, 1988). We report a particularly severe clinical problem produced by the combination of toluene intoxication and diabetic ketoacidosis.